Konsep Ridhâ Allah dalam Diskursus Pendidikan Islam - Azis, Abdul; Rizal, Soni Samsu (TAJDID, 2019)
The aims of this article are to discover the concept of mardlati ‘l llah (the pleasure of Allah) and its implication on education. The concept of ridla Allah in Koran is refer to seven meanings. There are al-amr bi al-ma’ruf (command what is just) and nahy ‘an al-munkar (forbid what is evil); jihad in the way of Allah; fear and hope in Allah; spend of our substance and donation for the poor and the needy in the cause of Allah; work righteous deeds; reconciliation between groups in conflict; and believe in qadha and qadar Allah. These seven concepts, according to this research, are closely related to the idea of character education which is currently becoming an important issue ini contemporary education